2014
DOI: 10.1242/jeb.107516
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced depolarization of insect muscle: Differing roles of extracellular K+ during acute and chronic chilling

Abstract: Insects enter chill coma, a reversible state of paralysis, at temperatures below their critical thermal minimum (CT min ), and the time required for an insect to recover after a cold exposure is termed chill coma recovery time (CCRT). The CT min and CCRT are both important metrics of insect cold tolerance that are used interchangeably, although chill coma recovery is not necessarily permitted by a direct reversal of the mechanism causing chill coma onset. Nevertheless, onset and recovery of coma have been attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 51 publications
(81 reference statements)
13
111
1
Order By: Relevance
“…Numerous studies have shown how chronic cold stress changes hemolymph [K + ] and [Na + ] in locusts Findsen et al, 2013) and other insects (Koštál et al, 2004(Koštál et al, , 2006MacMillan and Sinclair, 2011b;MacMillan et al, 2014MacMillan et al, , 2015bCoello Alvarado et al, 2015;Des Marteaux and Sinclair, 2016) and consistent with these earlier observations we found that ion balance of locusts was disrupted during prolonged cold stress (≥4 h). Specifically we found that muscle ion concentrations generally remained constant (Fig.…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stresssupporting
confidence: 90%
See 4 more Smart Citations
“…Numerous studies have shown how chronic cold stress changes hemolymph [K + ] and [Na + ] in locusts Findsen et al, 2013) and other insects (Koštál et al, 2004(Koštál et al, , 2006MacMillan and Sinclair, 2011b;MacMillan et al, 2014MacMillan et al, , 2015bCoello Alvarado et al, 2015;Des Marteaux and Sinclair, 2016) and consistent with these earlier observations we found that ion balance of locusts was disrupted during prolonged cold stress (≥4 h). Specifically we found that muscle ion concentrations generally remained constant (Fig.…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stresssupporting
confidence: 90%
“…As previously observed in cold-stressed locusts, we found that E K depolarized considerably, while E Na remained fairly constant during the prolonged cold stress (Fig. 2C,F) (MacMillan et al, 2014). Cold-acclimated locusts retained a more polarized E K than their warm-acclimated conspecifics because they were able to better maintain transmembrane K + balance, a pattern also observed in crickets (Coello Alvarado et al, 2015), fire bugs (Koštál et al, 2004), and cockroaches (Koštál et al, 2006).…”
Section: Cold Acclimation Improves Ion Homeostasis During Cold Stresssupporting
confidence: 89%
See 3 more Smart Citations